NON-MONETARY INCENTIVES AND ORGANISATIONAL CITIZENSHIP BEHAVIOUR: EVIDENCE FROM NIGERIA HOSPITALITY INDUSTRY - Kamorudeen Abimbola Oyetola; Zacchaeus O. Olonade; Solomon Ojo (Sampoerna University, 2026)
The current economic conditions caused by unfavourable and uncertain government policies have made it difficult for most organisations to influence employees’ behaviour positively. This development has made it extremely hard for them to survive over time. The study, therefore, examined the influence of non-monetary incentives on organisational citizenship behaviour using the staff of selected hotels within Osogbo as the unit of analysis. The specific objectives were to investigate the influence of employee job recognition on sportsmanship behaviour and to determine the influence of conducive work environment on courtesy behaviour. The study was survey research that employed descriptive design. The study population was one hundred and fifty-five (155), which comprised the employees of the selected hotels (Leisure Spring Hotel, Ideal Nest Hotel, and Royal Continental Hotel). Data was collected from primary source and with the aid of structured questionnaire. Hypotheses were tested using linear regression and with the aid of Statistical Package for Social Sciences (SPSS Version 23.0). Findings revealed that employee job recognition positively influenced sportsmanship behaviour. Conducive work environment positively influenced courtesy behaviour. The study concluded that there was a positive relationship between non-monetary incentives and organisational citizenship behaviour in selected hotels within Osogbo. The study recommends that appropriate incentives should be apportioned to the employees, which will spur them to go beyond their job roles pertinent for survival and growth.